The ABC transporters of human physiology and disease : genetics and biochemistry of ATP binding cassette transporters - Linton, Kenneth J.; Holland, I. B. (World Scientific, 2011)
ATP Binding Cassette (ABC) transporters are a family of integral membrane proteins present in all cells of all species of archaea, eubacteria and eukaryota. The vast majority of these proteins control the transport across cellular membranes of molecules ranging from small ions to drugs, lipids and proteins. The human genome encodes 48 ABC transporter genes and mutations in most have been linked to disease. This book - that brings together state-of-the-art knowledge on ABC proteins in one volume - will provide students, professors and medical professionals with a background to the human ABC transporters that are known to be relevant to disease. Each of the 14 chapters is written by a leading researcher in the field. The genetics, structure and function of the proteins, and the future direction of research including the implications for human health are discussed in depth.